2013
DOI: 10.1179/108331913x13608385943254
|View full text |Cite
|
Sign up to set email alerts
|

Association between glenohumeral subluxation and hemiplegic shoulder pain in patients with stroke

Abstract: Background: Glenohumeral subluxation (GHS) and hemiplegic shoulder pain (HSP) are the most common musculoskeletal complications reported in patients with stroke. These secondary problems present considerable challenges to the rehabilitation of the upper limb. Objective: The aim of this review was to evaluate the evidence on the association between shoulder subluxation and pain in patients with stroke. Method: A systematic online search was conducted of MEDLINE, EMBASE, CINAHL, AMED, Biomed Central, and the Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…Association between glenohumeral subluxation (GHS) and HSP has been a controversial issue. Of 14 studies included in a systematic literature review, seven showed an association while another seven showed no association, suggesting that not all patients with GHS necessarily experience shoulder pain [13]. Findings on the association between subluxation and pain are controversial and this may be attributable, in part, to the methodological differences of the studies reviewed.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Association between glenohumeral subluxation (GHS) and HSP has been a controversial issue. Of 14 studies included in a systematic literature review, seven showed an association while another seven showed no association, suggesting that not all patients with GHS necessarily experience shoulder pain [13]. Findings on the association between subluxation and pain are controversial and this may be attributable, in part, to the methodological differences of the studies reviewed.…”
Section: Risk Factorsmentioning
confidence: 99%
“…did not find association. The writers had an opinion that this area lack high quality clinical research [4]. 100 individuals that formed a 500 subjects for survey.…”
Section: Study Rationalmentioning
confidence: 99%
“…Spasticity is associated with decreased function due to abnormal patterns of movement, co-contraction of muscles, associated movements and persistent limb posturing, and the development of contractures (Marciniak, 2011). Spasticity has also been associated with HSP (Kumar, Saunders, Ellis, & Whitlam, 2013;Lindgren et al, 2007;Rajaratnam et al, 2008) and glenohumeral joint subluxation (Ada & Foongchomcheay, 2002;Kumar, Kassam, Denton, Taylor, & Chatterley, 2010;Stolzenberg et al, 2012). In summary, evidence points to both flaccidity and spasticity being associated with HSP and subluxation.…”
Section: Sensorimotor Deficits and Recoverymentioning
confidence: 99%
“…The association between shoulder pain, muscle tonus and subluxation has been investigated within several reviews (Kumar et al, 2013;Murie-Fernández et al, 2012;Paci et al, 2005), though the reviews remain equivocal about these associations. This lack of consensus could be attributable to whether recruitment and data collection occurred in the acute, subacute or chronic phase or a combination of these.…”
Section: Glenohumeral Subluxationmentioning
confidence: 99%